Sexual offending hierarchies, personality attributions, and the clinical implications - Challinor, Laura Elizabeth; Duff, Simon (Emerald, 2017)
Aims: the research examines sexual offending hierarchies constructed by the general public and forensic staff based on personal attitudes and perceived severity of offence. In addition, six sexual offence perpetrators are differentiated using the Five Factor Model of personality. Method: vignettes represented six sexual offence perpetrators. Participants built a hierarchy based on perceived severity of offence, before attributing personality characteristics to each offender using a Likert-type scale. Results: contact offenders were perceived as more dangerous than non-contact offenders. Rapists were perceived as the most dangerous, and voyeurs the least dangerous. Offenders were attributed significantly different personality traits. Generally, men who sexually offend are perceived to be low in agreeableness, openness and conscientiousness and high in impulsivity, manipulativeness and neuroticism. Practical Implications: the research highlights the importance of individual risk assessment in determining best practice treatment for men who have sexually offended. The Five Factor Model has been proven to be a useful tool to explore the impact staff attitudes have on risk assessment and treatment. Low-risk and high-risk men who have sexually offended would benefit from divergent treatment. Consideration should be given to personality characteristics in addition to level of risk. Originality: The research determines a hierarchy of men who sexually offend, and goes beyond the 'label' of sexual offenders to explore how personality impacts on formation of attitudes.